What Makes Society Happy? Exploring Factors Influencing Happiness in Indonesia - Toni Andreas Susanto; Muliati Muliati (Universitas Negeri Semarang, 2025)
Happiness is a crucial aspect in evaluating development, as it reflects both the output and outcome for society. This study aims to examine the influence of environmental quality index (IKLH), human development index (IPM), economic growth, and government expenditure on the happiness index of Indonesia and 34 provinces in Indonesia. A panel data regression model is employed to identify the factors of Indonesia’s happiness index, while Geographically Weighted Panel Regression (GWPR) is specifically for 34 provinces in Indonesia. This model combination introduces a novel methodology for happiness studies by providing a comprehensive perspective. Both models produce consistent relationships and significant variables: IKLH has a significant negative relationship, while IPM and economic growth have significant positive relationships, but government expenditure is not significant. Specifically, the GWPR indicate that happiness in Kalimantan Island, parts of Sumatra, South Sulawesi, and Bali is influenced solely by IPM. The happiness of most provinces in Sumatra and the Nusa Tenggara Islands is driven by IPM and economic growth. Meanwhile, all provinces in Java Island, Lampung, North Maluku, and most of Sulawesi Island, have happiness influenced by IPM and IKLH. Finally, in the majority of eastern Indonesian provinces, happiness is shaped by IPM, IKLH, and economic growth.